Integrated Marketing Communication Strategies and Rebranding of Telkom Kenya - Kamau, Faith; Mberia, Hellen; Ndavula, John (International Journal of Communication and Public Relation, 2023)
Purpose: The aim of this study was to establish the effectiveness of integrated marketing communication strategies on rebranding of Telkom Kenya from Orange. Methodology: Questionnaires and interview guides were used to obtain qualitative and quantitative data with most of the quantitative data collected through questionnaires administered to the 80 respondents, representing subscribers. The questionnaires were administered online through Google Forms while one on one interview sessions with the key informants from Telkom Kenya conducted using interviews guides. Collected data was cleaned, coded and entered into the computer for analysis using the Statistical Package for Social Sciences (SPSS) Version 21. The data was analyzed using descriptive and inferential statistical approaches. Qualitative data was analyzed through thematic analysis. Findings were presented in table, graph and narrative text formats. Findings: Key finding was that the joint effect of advertising, sales promotion, direct marketing and other forms of IMC was significant on the success of rebranding in Telkom Kenya. Regression analysis of the variables showed that sales promotion (p=.004) and direct marketing (p=.028) were significant (p<0.05) compared to advertisement whose effect on rebranding was 0.138 i.e. p>0.05. Unique Contribution to Theory, Practice and Policy: The theory of persuasion may anchor future studies in the telecommunication providers. The study recommends that the telecommunication companies need not only to plan their rebranding but to ensure that they embrace IMC that is driven through application of current information and communication technologies. Collaboration with the government is vital in crafting a regulatory framework that fosters fair competition and supports the telecommunications industry's growth. Engaging in dialogue with regulatory authorities will also help address any potential barriers to the company's rebranding efforts and ensure compliance with relevant policies. Furthermore, the government's involvement in public awareness campaigns can help promote the rebranded Telkom Kenya as a trusted and reliable player in the market. This collaboration could include joint initiatives to expand telecommunication infrastructure, enhance digital literacy, and bridge the digital divide, thereby showcasing Telkom Kenya's commitment to national development goals.